The Effect of Durus al-Lughah al-Arabiyyah Volume One on Arabic Reading Skills of Eighth-Grade Students - Liya Minkhatul Maula; Mokhammad Miftakhul Huda; Suharia Sarif (Pasca Sarjana IAIN Sultan Amai Gorontalo, 2026)
Media refers to all forms and channels used to deliver messages or information as a communication tool in the teaching process to transfer knowledge from teachers to students, encouraging active participation in learning. The use of the book “Durus al-Lughah al-‘Arabiyyah” Part One is considered to support the development of reading skills among eighth-grade students. This study aims to determine the effect of using this book as a learning medium on students’ reading skills before and after treatment, and to measure the extent of its effectiveness among eighth-grade “B” students at Al-Misri Islamic Junior High School, Rambipuji, Jember. This research employed a quantitative experimental within a one-group pretest-posttest design approach using descriptive and inferential statistical analysis. The population consisted of 104 students, while the sample included all 27 students of class VIII “B” in the 2023/2024 academic year. Data were analyzed through simple linear regression and determination coefficient testing. The simple linear regression test showed a significance value of 0.000 (<0.05), indicating a significant effect of using the book as a learning medium on reading skills. The R-Square value reached 0.897, demonstrating that the medium contributed 89.7% to the improvement of reading ability. The findings indicate a statistically significant improvement after the intervention; however, further controlled studies are needed to establish causal effectiveness.